Metabolic Health Status Contributes to Transcriptome Alternation in Human Visceral Adipose Tissue During Obesity. Issue 11 (27th September 2020) - Zhou, Qiuzhong; Fu, Zhenzhen; Gong, Yingyun; Seshachalam, Veerabrahma Pratap; Li, Jia; Ma, Yizhe; Liang, Hui; Guan, Wei; Lin, Shibo; Ghosh, Sujoy; Sun, Lei; Zhou, Hongwen
Abstract : Objective: BMI is a well‐established factor affecting the transcriptome profile of adipose tissue, but there are few reports on the relationship between the metabolic health status of people with obesity and the transcriptional changes, particularly in visceral adipose tissue. Methods: Visceral adipose tissue was collected from three subgroups of patients, lean ( n = 11), metabolically healthy obesity (MHO; n = 22), and metabolically unhealthy obesity (MUO; n = 26), and RNA sequencing was conducted to profile the transcriptome changes between these groups in a pairwise manner. Results: Comparing MUO with lean and comparing MHO with lean revealed similar patterns in gene expression and pathway changes: obesity, regardless of metabolic health, was associated with upregulated inflammatory pathways. However, the inflammatory signature in MUO was stronger than in MHO. Pairwise comparisons among MUO, MHO, and lean samples identified 34 common differentially expressed genes; 12 out of 34 genes were associated with inflammatory pathways and exhibited a gradually increased expression pattern in the order of lean, MHO, and MUO. Conclusions: This study reveals not only that BMI plays an important role in determining the gene expression profile in visceral adipose tissue but also that a metabolically healthy condition is associated with a less inflammatory transcriptional change during obesity.